Body Roundness Index (BRI) Predicts Metabolic Syndrome in Postmenopausal Women with Obesity Better than Insulin Resistance - Daniel de Luis; Marife Muñoz; Olatz Izaola; Juan José Lopez Gomez; Daniel Rico; David Primo (Diabetology, 2025)
Background/Objective: The body roundness index (BRI) has emerged as a novel anthropometric parameter with potential utility in the assessment of obesity and its associated metabolic complications. This study aimed to identify the optimal BRI cut-off point for the diagnostic process of metabolic syndrome (MetS) in a cohort of postmenopausal women with obesity and to compare its predictive capacity with that of the homeostasis model assessment of insulin resistance (HOMA-IR). Methods: A cross-sectional analysis was conducted in 468 Caucasian postmenopausal women with obesity. Clinical and biochemical assessments included anthropometric measurements, blood pressure, fasting plasma glucose, insulin levels, the HOMA-IR, lipid profile, C-reactive protein, and adipokines. MetS was diagnosed according to the Adult Treatment Panel III (ATP III) criteria. Results: MetS was identified in 270 patients (57.5%). Stratification by the median BRI revealed that individuals in the higher-BRI group had a significantly increased odds of MetS (OR 2.65; 95% CI: 1.99–3.53; p = 0.03). A Receiver Operating Characteristic (ROC) curve analysis showed that the HOMA-IR had an area under the curve (AUC) of 0.72 (95% CI: 0.67–0.77; p = 0.01), with a cut-off value of 2.64 (sensitivity: 64.9%; specificity: 69.7%). In contrast, the BRI exhibited a higher AUC of 0.75 (95% CI: 0.71–0.80; p = 0.001), with an optimal cut-off of 8.15, demonstrating superior sensitivity (85.6%) and specificity (72.5%). Conclusions: The BRI is a promising and practical alternative anthropometric index for identifying MetS in Caucasian postmenopausal women with obesity. Its strong association with markers of adiposity and metabolic dysregulation underscores its potential value in clinical and epidemiological settings.